The influence of recall direction on judgments of subjective temporal distance from the beginning of the COVID-19 pandemic lockdowns - Dantzler, Connor; Markman, Keith D. (Frontiers in Social Psychology, 2024)
Introduction In a series of 5 studies, Lam and Buehler found that first-year university students felt closer to a target event (the day they learned that they were accepted into university) when they recalled a stream of related events in a backward direction (a reverse-chronological order ending with the target event) than when they recalled those events in a forward direction (a forward-chronological order beginning with the target event). Methods In a conceptual replication of their Study 2, we asked participants how close they felt to the first day that lockdowns were imposed in response to the Covid-19 pandemic in the U.S. (federally mandated on March 13, 2020) following either backward or forward recall of a stream of related events. Results The results of the present study ran directly counter to those of Lam and Buehler: participants rated the first day of lockdowns as feeling closer following forward recall than following backward recall. Discussion Potential explanations for this reversal of Lam and Buehler's effect are discussed that focus on the temporal distortions that people have been found to experience when they think about autobiographical events that occurred at the beginning of the pandemic.